Developing a Government Hub for Smart Governance and Accelerating Digital Public Service Transformation in Bone Regency - Muslimin Muslimin (Universitas Cahaya Prima, 2024)
The development of a Government Hub in Bone Regency represents a strategic effort to accelerate digital transformation and strengthen innovation in public service delivery. This study aims to examine the implementation of the Government Hub, identify key indicators of success, and formulate sustainable development strategies to support modern governance. A qualitative approach employing the Simple Research Design (SRD) framework was adopted through literature review, in-depth interviews, and document analysis. Data were analyzed using the Context, Input, Process, Product (CIPP) evaluation model to assess program effectiveness comprehensively, while a system dynamics approach was utilized to understand causal relationships among variables affecting implementation. The findings indicate that the Government Hub contributes significantly to improving administrative efficiency, expanding access to digital public services, strengthening transparency and accountability, and supporting local economic development through the empowerment of micro, small, and medium enterprises and tourism sectors. The study also reveals that the sustainability of the initiative depends on adequate digital infrastructure, adaptive human resources, effective inter-institutional collaboration, and strong data governance. Despite challenges related to technological disparities and organizational resistance, the Government Hub has demonstrated its potential as a catalyst for socio-technical transformation. The study concludes that the Government Hub is not merely a technological innovation but a strategic framework for promoting inclusive, transparent, and sustainable governance in Bone Regency.